Constructing 'the Best Interests of the Child' in Digital Space Governance: A Critical Discourse Analysis of Government Regulation No. 17 of 2025 - Atef Fahrudin (Penerbit Jurnal Indonesia, 2026)
This study aims to examine how the concept of